A Study on the Role of Additives in Non-Cyanide Baths for the Fabrication of Anisotropic Metallic Nanostructures. (25th October 2017) - Dhingra, Kabir; Gupta, Somya; Sarupria, Manan; Nambi Krishnan, Jegatha; Kumar, Siddharth
Abstract : In this study, bath solutions have been prepared for synthesis of gold nanostructures. The role of different additives in bath formulations and their effects on gold nanostructures has been investigated. Synthesis of gold nanostructures through electroless deposition is widely performed using cyanide baths. Here, two non-cyanide gold solutions (bath A and B) are prepared in house and a commercial cyanide gold plating solution (bath C) is used. The 2-Mercaptobenzothiazole that may act as a stabilizing agent is added in Bath A. The Na L-Ascorbate that is a reducing agent is added in bath B. The zeta potential analysis was carried out that exhibited bath B as the most stable formulation. A variety of metallic substrates like silver, copper and nickel have been studied. The surface morphology of metallic substrates was characterized using SEM technique. Anisotropic gold nanostructures of different shapes like star, spherical, dendrite, polyhedral were achieved using non-cyanide baths.